Reducing Inbound Logistics Costs- A Case Study in the Chinese Automobile Industry - Feng, Mengying (2006)
Globalization has made company competition more intense. Supply chain management has developed to enable companies to compete effectively. Logistics supports competitiveness of the supply chain as a whole by meeting customer demand both timely and at a competitive cost and inbound logistics cost management is considered to be a priority in reducing costs.